In vivo vascular rarefaction and hypertension induced by dexamethasone are related to phosphatase PTP1B activation not endothelial metabolic changes - Herrera, Naiara Araújo [UNESP]; Duchatsch, Francine [UNESP]; Kahlke, Allison; Amaral, Sandra Lia [UNESP]; Vasquez-Vivar, Jeannette (Elsevier, 2020)
Glucocorticoids have important anti-inflammatory and immunomodulatory activities. Dexamethasone (Dex), a synthetic glucocorticoid, induces insulin resistance, hyperglycemia, and hypertension. The hypertensive mechanisms of Dex are not well understood. Previously, we showed that exercise training prior to Dex treatment significantly decreases blood vessel loss and hypertension in rats. In this study, we examined whether the salutary effects of exercise are associated with an enhanced metabolic profile. Analysis of the NAD and ATP content in the tibialis anterior muscle of trained and non-trained animals indicated that exercise increases both NAD and ATP; however, Dex treatment had no effect on any of the experimental groups. Likewise, Dex did not change NAD and ATP in cultured endothelial cells following 24 h and 48 h of incubation with high concentrations. Reduced VEGF-stimulated NO production, however, was verified in endothelial cultured cells. Reduced NO was not associated with changes in survival or the BH4 to BH2 ratio. Moreover, Dex had no effect on bradykinin- or shear-stress-stimulated NO production, indicating that VEGF-stimulated eNOS phosphorylation is a target of Dex's effects. The PTP1B inhibitor increased NO in Dex-treated cells in a dose-dependent fashion, an effect that was replicated by the glucocorticoid receptor inhibitor, RU486. In combination, these results indicate that Dex-induced endothelial dysfunction is mediated by glucocorticoid receptor and PTP1B activation. Moreover, since exercise reduces the expression of PTP1B and normalized insulin resistance in aging rats, our findings indicate that exercise training by reducing PTP1B activity counteracts Dex-induced hypertension in vivo.
Keywords: Endothelial dysfunction; Glucocorticoid receptor; Nitric oxide; VEGF